2018
DOI: 10.1093/carcin/bgy068
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of single cell-derived colorectal cancer cell lines is dominated by the continued selection of tumor-specific genomic imbalances, despite random chromosomal instability

Abstract: Intratumor heterogeneity is a major challenge in cancer treatment. To decipher patterns of chromosomal heterogeneity, we analyzed six colorectal cancer cell lines by multiplex interphase FISH (miFISH). The mismatch repair deficient cell lines DLD-1 and HCT116 had the most stable copy numbers, whereas aneuploid cell lines (HT-29, SW480, SW620 and H508) displayed a higher degree of instability. We subsequently assessed the clonal evolution of single cells in two CRC cell lines, SW480 and HT-29, which both have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Analysis of established cell lines has not captured this heterogeneity, presumably because long-term cell culture selects the fitter, more stable subclones. Indeed, clonal evolution analysis of established colorectal cancer cells shows that despite persistent chromosome segregation errors, specific karyotypes are maintained 52 , and while multipolar spindles were prevalent in the OCMs, established ovarian cancer cell lines typically undergo bipolar divisions. Another advantage of viable cultures is the ability to analyse highly purified tumour fractions unfettered by contaminating, genetically normal stromal cells and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of established cell lines has not captured this heterogeneity, presumably because long-term cell culture selects the fitter, more stable subclones. Indeed, clonal evolution analysis of established colorectal cancer cells shows that despite persistent chromosome segregation errors, specific karyotypes are maintained 52 , and while multipolar spindles were prevalent in the OCMs, established ovarian cancer cell lines typically undergo bipolar divisions. Another advantage of viable cultures is the ability to analyse highly purified tumour fractions unfettered by contaminating, genetically normal stromal cells and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to the second question is less clear‐cut. Major features of genome stability such as the rate of new copy number alterations are usually preserved even during long term culture and in lines originating from single subcultures (so‐called sublines) . The preservation of the original rate of clonal evolution together with the inherent resilience of intracellular signalling networks may explain why cell lines even after long term passage may preserve response rates to chemotherapeutic drugs that parallel those seen in the corresponding tumor type, albeit not with a precision that is useful to the individual patient .…”
Section: The Utility Of Cell Lines In Light Of Clonal Evolutionmentioning
confidence: 99%
“…For example, the expansion of subclonal cells with genotypes that have evolved further from the stem line can dramatically increase the number of novel genetic aberrations in the cell culture . Furthermore, cancer cell lines derived from single cells of the same bulk population may exhibit different rates of chromosomal instability, as well as ploidy, gene expression, and tumorigenicity . Interestingly, at least one study has shown that single cell clones generally display reduced efficiency of tumor formation in mice compared to bulk parental cells even though the majority of genomic imbalances and monitored oncogene mutations are preserved in the single cell clones .…”
Section: The Population Bottleneck Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitous cellular heterogeneity in tumors may suggest that cooperative interactions between distinct subsets of cells must be present in order to maintain the observed heterogeneity (5,50) Recent work by Marusyk et al (6) has found evidence for non-cell autonomous proliferation using a mathematical modeling framework, showing that the null hypothesis of no clonal interactions can be easily rejected in favor of a model that considers a specific clone that helps support the growth of all other clones. Additionally, studies in which clonal diversity has been manipulated by combining clones in culture have demonstrated that the presence of diverse clones is necessary to obtain the observed growth rate achieved in multi-clonal parental cell cultures (51).…”
Section: Discussionmentioning
confidence: 99%